DAMPAK SOSIAL AI TERHADAP PEMBELAJARAN BAHASA - Dewi Sakinah (Jurnal Sastra - Studi Ilmiah Sastra, 2025)
The rapid advancement of Artificial Intelligence (AI) has significantly transformed various fields, including language learning. AI provides easier access to information, personalized learning experiences, and increased motivation and interactivity through digital platforms such as ChatGPT, Duolingo, Google Translate, and other applications. However, its use also raises social challenges, including overdependence, reduced human interaction, digital inequality, and ethical concerns related to privacy and cultural bias. This study aims to analyze the social impacts of AI on language learning, both positive and negative, as well as to explore learners’ perceptions of AI as a learning aid. Using a theoretical review and literature-based analysis, the study reveals that AI contributes to broader access and the democratization of language education, yet requires careful management to avoid diminishing critical thinking skills and the value of human interaction. The findings are expected to provide theoretical contributions to language education studies and practical recommendations for educators, learners, and educational institutions in integrating AI into language learning ethically, effectively, and in a balanced manner.